Models and Methods to Detect Similarity of Manufacturing Machines (Hungarian Journal of Industry and Chemistry, 2010)
This paper focuses on detecting similarity of Manufacturing machines. It discusses the application of the Group Technology (GT) concept in the case of producing controller software for manufacturing machines. An overview on the modular machines is given. The paper presents a new concept for the development of the controllers’ software. The advantages of GT are presented. Two grouping approaches are detailed: the bottom-up approach and the top-down approach. A Genetic Algorithm Clustering is presented for the automatic grouping. The second part of the paper deals with the similairity of PLC code. Smith and Waterman local allignment search algorithm is used to detect similar code paths in PLC programs.
Keywords: Group Technology; Genetic Algorithm Clustering; Code similarity; Smith Waterman algorithm